2020
DOI: 10.1021/acssuschemeng.0c03745
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Trifluoromethylation/Cyclization of 1,7-Enynes in Continuous Flow

Abstract: In the present study, we describe the successful development of a photoredox-catalyzed trifluoromethylation/ cyclization of 1,7-enynes in a continuous-flow regime for the generation of several CF 3 -containing heterocyclic scaffolds. When using this protocol, a readily prepared Ph 2 SCF 3 OTf reagent was employed as the trifluoromethylation reagent, and various benzo-[j]phenanthridines and indeno[1,2-c]quinolines were obtained in good to moderate yields. This transformation featured mild reaction conditions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…Under continuous flow conditions, Qiu, Guo, and co-workers in 2020, demonstrated a photoredox catalysed trifluoromethylation and cyclization of 1,7-enynes (138 and 130), affording the CF 3 -containing benzo[j]phenanthridines 140 and indeno[1,2-c]quinolines 141 in good yields (Scheme 44). [98] In this protocol, the fac-Ir(ppy) 3 photoredox-catalyst was employed along with Yagupolskii-Shreeve reagent (Ph 2 SCF 3 OTf) 139 as a trifluoromethyl radical precursor, 2,6-lutidine as a base, in CH 2 Cl 2 under visible light irradiation. Notably, the benzyl (Bn) group on the alkenyl part of 1,7-enynes 138 gave benzo Thereafter, a similar tactic was developed by Zhang, Song, Wang, and co-workers for the synthesis of fused monofluorinated cyclopenta [c]quinoline-4-ones 143 with good diastereoselectivity by comprising BrCHFCO 2 Et 142 as a * CHFCO 2 Et radical precursor (Scheme 45a).…”
Section: Dienynes and Enediynesmentioning
confidence: 99%
“…Under continuous flow conditions, Qiu, Guo, and co-workers in 2020, demonstrated a photoredox catalysed trifluoromethylation and cyclization of 1,7-enynes (138 and 130), affording the CF 3 -containing benzo[j]phenanthridines 140 and indeno[1,2-c]quinolines 141 in good yields (Scheme 44). [98] In this protocol, the fac-Ir(ppy) 3 photoredox-catalyst was employed along with Yagupolskii-Shreeve reagent (Ph 2 SCF 3 OTf) 139 as a trifluoromethyl radical precursor, 2,6-lutidine as a base, in CH 2 Cl 2 under visible light irradiation. Notably, the benzyl (Bn) group on the alkenyl part of 1,7-enynes 138 gave benzo Thereafter, a similar tactic was developed by Zhang, Song, Wang, and co-workers for the synthesis of fused monofluorinated cyclopenta [c]quinoline-4-ones 143 with good diastereoselectivity by comprising BrCHFCO 2 Et 142 as a * CHFCO 2 Et radical precursor (Scheme 45a).…”
Section: Dienynes and Enediynesmentioning
confidence: 99%
“…On the basis of related literature reports , and the above-mentioned observations, we proposed a possible mechanism for this photocatalyzed fluoroalkylation/cyclization reaction (Scheme ). Initially, photocatalyst PC (4CzIPN) excited by visible light irradiation ( PC* ) reduced Ph 2 SCF 3 OTf generate a CF 3 radical by way of a single electron transfer (SET) process.…”
mentioning
confidence: 95%
“…The methods for the incorporation of fluorine atoms into organic molecules have attracted considerable attention because the fluorine-containing compounds widely exist in pharmaceuticals and agrochemicals and materials. However, almost all of the classical protocols suffer from harsh conditions and require expensive metal catalysts or toxic solvents . On the other hand, visible-light photoredox catalysis also offers a novel and efficient method to access the construction of fluoro-containing heterocycles. , Recently, practical fluoralkylation has been realized by the action of visible-light catalysis on a variety of fluorinating sources such as Togni, Umemoto, and Langlois reagents. Well-designed sources of CF 3 /CF 2 H are still not available, as recent studies have highlighted the problems with the currently available ones. , Moreover, we previously reported a useful method for carrying out trifluoromethylations/cyclizations of 1,7-enynes by using Ph 2 SCF 3 OTf as a CF 3 source in continuous flow . In 2017, Akita and co-workers reported a shelf-stable easy-to-handle sulfonium salt, namely, Ph 2 SCF 2 HBF 4 ( S -difluoromethyl- S -di­( p -xylyl)­sulfonium tetrafluoroborate) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The difluorolative functionalization reaction emerges as a highly efficient strategy to access various of difluoromethylene-containing organic molecules. , The commercially available sources iodofluoroiodoacetate and bromodifluoroacetate have been reported with a combination of various transition-metal catalysts to generate the difluoroalkyl carbon radicals. Most of the examples indicated that the bromine and iodine atoms were not incorporated into the final products . With regard to the atom economy, installing both the bromine or iodine atoms and a difluoromethylene-containing group would be more desirable.…”
mentioning
confidence: 99%